2014
DOI: 10.1007/s00280-014-2632-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of CYP2B6 genetic polymorphisms in patients receiving cyclophosphamide combination chemotherapy for breast cancer

Abstract: This is the first report on the pharmacogenetic profile of patients with breast cancer and the therapeutic and myelo-toxic behavior of CP in women from an Arab Middle Eastern country. Our results show that genotyping for these CYP2B6 alleles does not help in personalizing therapy from a toxicity perspective, and the association of shorter survival in these subjects with homozygous variants is interesting yet insufficient to justify routine genotyping prior to therapy, or to consider using a higher CP dose. Lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…To further improve outcomes, the development of specific therapeutic protocols based on individuals’ genetic profiles is essential. Moreover, genetic polymorphisms were shown to affect neutrophil counts in patients who are administered DOX-based chemotherapy [22]; in these studies, the emergence of chemotherapy-induced severe toxicities was more frequent in Asian patients than in Western patients, suggesting that the former are more susceptible to febrile neutropenia.…”
Section: Discussionmentioning
confidence: 99%
“…To further improve outcomes, the development of specific therapeutic protocols based on individuals’ genetic profiles is essential. Moreover, genetic polymorphisms were shown to affect neutrophil counts in patients who are administered DOX-based chemotherapy [22]; in these studies, the emergence of chemotherapy-induced severe toxicities was more frequent in Asian patients than in Western patients, suggesting that the former are more susceptible to febrile neutropenia.…”
Section: Discussionmentioning
confidence: 99%
“…A study of CYP2B6 haplotypes in 38 breast cancer patients found a significant gene‐dose relationship and time to relapse, while no association was observed with outcomes and CYP2B6 haplotypes in a larger cohort of breast cancer patients ( n = 350) . However, although this study did not assess CYP2C19 , disease‐free survival was associated ( P = 0.02, unadjusted) with CYP3A4*1B .…”
Section: Therapeutic Outcomesmentioning
confidence: 57%
“…CYP2B6*6 was found to have a protective effect from high grades neutropenia (Tsuji et al, 2016). However, the same haplotype, determined by rs3745274, did not show any significant association when the need for dose reduction, erythropoietin use, transfusion, or iron supplementation was considered as the studied outcomes (Haroun et al, 2015).…”
Section: Slco1b3 Cyp2c8 Abcb1mentioning
confidence: 89%